Design and Experimental Analysis of Multiband Compound Reconfigurable 5G Antenna for Sub-6 GHz Wireless Applications. (20th April 2021) - Ahmad, Ikhlas; Dildar, Haris; Khan, Wasi Ur Rehman; Shah, Syed Amir Ali; Ullah, Shakir; Ullah, Sadiq; Umar, Syed Muhammad; Albreem, Mahmoud A.; Alsharif, Mohammed H.; Vasudevan, Kasturi
Abstract : In this paper, a printed low-profile antenna with frequency and pattern reconfigurable functionality is designed in three modes. Each mode operates at different frequency bands and has several options available for pattern reconfiguration in these bands. The proposed antenna consists of eight pin-diode switches (S1 to S8). The switches S1 and S2, installed in the radiating patch, are used for frequency reconfigurability to control the operating bands of the antenna. The rest of the six switches (S3, S4, S5, S6, S7, and S8), loaded in the stubs on the rear side of the antenna, are used for pattern reconfiguration to control the main lobe beam steering. When all switches are off, the proposed antenna operates in a wideband mode, covering the 3.82-9.32 GHz frequency range. When S1 is on, the antenna resonates in the 3.5 GHz (3.09-4.17 GHz) band. When both S1 and S2 are on, the resonant band of the antenna is shifted to 2.5 GHz band (2.40-2.81 GHz). A very good impedance matching with a return loss of less than -10 dB is attained in these bands. The beam steering is done at each operating frequency by controlling the on and off states of the six pin-diode switches (S3, S4, S5, S6, S7, and S8). Depending on the state of the switches, the antenna can direct the beam in seven distinct directions at 4.2 GHz, 4.5 GHz, and 5 GHz. The main beam of the radiation pattern is steered in five different directions at 5.5 GHz, 3.5 GHz, and 2.6 GHz operating bands for the given state of the mentioned switches. The proposed antenna supports several sub-6 GHz 5G bands (2.6 GHz, 3.5 GHz, 4.2 GHz, 4.5 GHz, and 5 GHz) and can be used in handheld 5G devices.